Association Between Demodex Infestation and Ocular Surface Microbiota in Patients With Demodex Blepharitis - Yan, Yan; Yao, Qinke; Lu, Yang; Shao, Chunyi; Sun, Hao; Li, Yimin; Fu, Yao (Frontiers in Medicine, 2020)
Purpose: The aim of this study was to compare the ocular microbial communities in humans with and without demodex blepharitis in order to elucidate the relationship between ocular microorganisms and demodex infestation. Methods: Bacterial 16S rRNA genes of conjunctival sac samples from 30 demodex blepharitis patients and 14 healthy controls were sequenced using a pyrosequencing method, and their bacterial community structures were compared by bioinformatics. Results: Bacterial community clustering of conjunctival sac in the demodex blepharitis group were significantly distinct from the healthy control group, with significantly higher relative abundances of Firmicutes and Corynebacterium at the phyla level, as well as higher abundances of Lactobacillus and Bifidobacterium at the genus level. The relative abundance of Staphylococcus epidermidis (0.07–2.27%) was positively correlated with the demodex amount and modified OSDI. The major potential factors contribute to demodex blepharitis were Bacilli, Firmicutes, Cyanobacteria, Lactobacillus and Streptophyta. Conclusions: Patients with demodex blepharitis have varying degrees of bacterial microbiota imbalance in the conjunctival sac. Demodex serving as vectors to transfer both skin and environmental flora might be the potential mechanism. In addition, the number and type of demodex affect the specific ocular surface bacteria, presenting as ocular discomfort and obvious signs of blepharitis.